2001
DOI: 10.1159/000048766
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Nuclear Changes in FM3A Breast Tumor Cells after Epirubicin, Medroxyprogesterone and Tamoxifen Treatment in vitro

Abstract: Objective: Autophagy is a form of physiological programmed cell death which is observable after hormonal withdrawal. In this study, the FM3A murine breast tumor cell line was treated with epirubicin alone and with medroxyprogesterone acetate (MPA) or tamoxifen, to determine if structural and kinetic signs of autophagy may also occur in an enhanced manner during epirubicin sensitization via hormonal agents. Methods: One-week soft agar colony growth, 96-hour values of plating and pulse thymidine labeling and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…4,9) Some types of cancer exhibit autophagic changes after treatments with various anticancer agents. [47][48][49][50] Autophagic cell death is characterized by numerous autophagic vacuoles in the cytoplasm, 5,6) whereas the nucleus remains intact until the late stage of cell death. However, apoptosis is characterized by DNA condensation and fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…4,9) Some types of cancer exhibit autophagic changes after treatments with various anticancer agents. [47][48][49][50] Autophagic cell death is characterized by numerous autophagic vacuoles in the cytoplasm, 5,6) whereas the nucleus remains intact until the late stage of cell death. However, apoptosis is characterized by DNA condensation and fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…But few studies on the relationship between autophagy and chemotherapy were reported, especially studies utilizing resistant cancer cells. Bilir et al observed EPIinduced autophagy in FM3A murine breast tumor cells; 24 however, it remains unclear whether EPI may induce autophagy in MCF-7 cells and, if so, what is the significance of the possible autophagy, because the induction of autophagy is agent-dependent and the effects on cells would depend on the inducers and settings. 9 In this study, we hypothesized that EPI would induce autophagy in MCF-7 cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…An example of this is the antiestrogen tamoxifen, a drug that is currently in use clinically not only for its therapeutic benefits but also as an important tool in breast cancer chemoprevention strategies. Tamoxifen at a dose of 1 Amol/L has been reported to induce autophagy in human MCF-7 breast cancer cells, a response that was necessary for irreversible cell death to occur (101,(139)(140)(141)(142), although there is a recent report indicating a prosurvival action of autophagy in tamoxifen-treated cells (143). Interestingly, tamoxifen-induced autophagic vacuolization seems to be mediated by sphingolipid metabolites, including ceramide (124).…”
Section: Induction Of Autophagy and Cancer Cell Death By Chemotherapementioning
confidence: 99%